2020
DOI: 10.2174/1389201021666200320135139
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of MicroRNAs in the Bone Marrow of Multiple Myeloma Patients and their Relationship to Cytogenetic Aberrations

Abstract: Background: Multiple myeloma (MM) is a complex hematologic malignancy, driven by several genetic and epigenetic alterations. MiRNAs as biomarkers is a rapidly growing research area in the last decade. Aim of this study is to study the expression pattern of selected miRNAs and to explore the impact of cytogenetic aberrations in MM patients for therapeutic tools. Patients and methods: Forty Egyptian adult patients were selected for the study with symptomatic newly diagnosed MM disease. Bone marrow samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A wide array of studies have revealed cytogenetic and epigenetic changes in MM cells, which influence cellular proliferation, apoptosis, autophagy, and metastasis through different mechanisms, including the regulatory effects of microRNAs (miRNAs) on the progression of MM (5). miRNAs are small single-stranded RNAs (19)(20)(21)(22) nucleotide in length), which participate in various malignant biological processes of MM (6).…”
Section: Introductionmentioning
confidence: 99%
“…A wide array of studies have revealed cytogenetic and epigenetic changes in MM cells, which influence cellular proliferation, apoptosis, autophagy, and metastasis through different mechanisms, including the regulatory effects of microRNAs (miRNAs) on the progression of MM (5). miRNAs are small single-stranded RNAs (19)(20)(21)(22) nucleotide in length), which participate in various malignant biological processes of MM (6).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs regulate gene transcription activity by targeting miRNAs and have been reported to regulate physiological processes downstream, including cell viability, differentiation, apoptosis and carcinogenesis (39,40). As another type of non-coding RNA, miRNAs regulate the translation of target mRNAs by interacting with their 3'UTR (19)(20)(21). Numerous reports have confirmed that lncRNAs are miRNA sponges that indirectly affect the functions of mRNAs in multiple diseases (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) represent a family of highly conserved RNAs that are ~22 nucleotides in length. A number of studies have demonstrated that miRNAs regulate gene expression by pairing with the 3'-untranslated regions (UTR) of target mRNAs (19)(20)(21). miRNAs serve vital roles in numerous diseases by regulating gene expression, cell proliferation, inflammation, apoptosis and invasion (22)(23)(24), such that miRNA dysregulation has been previously associated with a number of human diseases (25).…”
Section: Role Of Lncrna Part1 In Intervertebral Disc Degeneration Andmentioning
confidence: 99%
“…It is recognized that epigenetic changes cooperate with genetic alterations to drive the malignant phenotype of MM. Specifically, aberrant DNA methylation, histone modification profiles [189][190][191][192], and abnormal microRNA (miRNA) expressions [193][194][195] have been demonstrated to be instrumental to MM pathogenesis.…”
Section: Proteasome Inhibitors and Epigenetic Drugs 371 Epigenetic Modifications As Druggable Targets In Multiple Myelomamentioning
confidence: 99%